A Pid Control System Using Ziegler-Nichols Method on Wheeled Soccer Robot Movement System - Hanifah Nur Ismail; Yulkifli Yulkifli; Rio Anshari; Dani Harmanto (RESSTECH, 2024)
The rapid advancement of robotics has impacted various sectors, including education. The Indonesian Robot Contest (KRI), organized by the Indonesian Talent Development Center, serves as a platform for innovation, featuring events like the Wheeled Indonesian Soccer Robot Contest (KRSBI-B). This study focuses on implementing a PID control system on a PG 45 type DC motor in a wheeled soccer robot, utilizing the Ziegler-Nichols method to determine optimal PID parameters. The goal is to design a stable PID control system and analyze how Kp, Ki, and Kd parameters influence robot movement. The research employs a scientific, rational, empirical, and systematic approach, using the Ziegler-Nichols method in quantitative research. The results demonstrate the successful design and implementation of the PID control system on the PG45 DC motor, with a rotary encoder used for RPM output and three-wheel kinematics for varied movements. While the Kp, Ki, and Kd values were optimal in motor tests without a load, some values failed to reach the setpoint during road tests due to additional motor load. Adjusting Kp, Ki, and Kd significantly affects the robot's movement, enhancing quick error response, reducing constant errors, and improving overshoot responsiveness. Future research should consider the test environment, use additional sensors for better data accuracy, and conduct repeated tests and evaluations to ensure system performance. This study offers practical and theoretical insights for the development of wheeled soccer robots and contributes significantly to future robotics research.